(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
تعد فطريات الصدأ التي تتبع لصف Basidiomycetes, تحت صف Sclerobasidiomyce- tidae, رتبة Uredinales, أكبر المجموعات الفطرية إجبارية التطفل على العديد من النباتات البرية والمزروعة, ومحاصيل الخضروات, والأشجار, ونباتات الزينة, من مغلفات وعريانات البذور تم القيام بجولات ميدانية دورية في مناطق مختلفة من محافظتي طرطوس واللاذقية, في الفترة بين 2008-2010, وتم جمع النباتات المصابة ومن ثم تحديد الأنواع الفطرية التابعة لفطريات الصدأ. أظهرت الدراسة وجود 67 نوعاً فطرياً يتبع إلى 9 أجناس مختلفة (43 نوعاً للجنس Puccinia, 10 أنواع للجنس Uromyces, 4 أنواع للجنس Melampsora, 3 أنواع للجنس Phragmidium, نوعان للجنس Tranzschelia, نوعان للجنس Coleosporium, ونوعاً واحداً لكل من الأجناس Aecidium, Cerotelium, Pileolaria) تتطفل على 91 عائلاً نباتياً, تنتمي إلى22 فصيلة نباتية. Rust fungi belonging to class Basidiomycetes, subclass Sclerobasidiomy-cetidae, order Uredinales, are considered a large group of obligate parasitic fungi on various wild and cultivated plants, including crops and ornamentals plants of Angiosperms as well as Gymnosperms. Field trips to various sites in Lattakia and Tartus provinces have been done in the period between 2008-2010 to determine the rust fungi infecting plants growing in these sites. Results showed the presence of 67 species belonging to 9 genera (43 species to Puccinia, 10 to Uromyces, 4 to Melampsora, 3 to Phragmidium, 2 to Tranzschelia, 2 to Coleosporium, and one to Aecidium, Cerotelium, and Pileoaria) parasitizing 91 plant species belonging to 22 plant families.